2013
DOI: 10.5665/sleep.2392
|View full text |Cite
|
Sign up to set email alerts
|

Adult-Onset NREM Parasomnia with Hypnopompic Hallucinatory Pain: A Case Report

Abstract: We report the case of a 43-year-old woman presenting with nocturnal episodes of pain and screaming during sleep starting at age 30. There was no childhood or family history of parasomnia. The events had gradually become more frequent over the years, occurring in the first half of the night within 2 h of sleep onset. There were no triggers, and she had partial amnesia for the events. A diagnosis of adult-onset sleep terrors was made on clinical grounds and supported polysomnographically. Seizures and periodic l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…An extensive review of the literature provides little insight into this phenomenon. One similar report comes from Mantoan et al [5], who reported adult-onset NREM parasomnia with hypnopompic hallucinatory pain. Similar to our case, the episodes arose within 1-2 h of sleep onset and were associated with looking terrified and initial lack of responsiveness.…”
Section: Discussionmentioning
confidence: 82%
“…An extensive review of the literature provides little insight into this phenomenon. One similar report comes from Mantoan et al [5], who reported adult-onset NREM parasomnia with hypnopompic hallucinatory pain. Similar to our case, the episodes arose within 1-2 h of sleep onset and were associated with looking terrified and initial lack of responsiveness.…”
Section: Discussionmentioning
confidence: 82%
“…The final analysis included 16 articles ( Figure 1 ). Seven articles were excluded during the full-article and data extraction stage: one because the reported dream mentation experience occurred following alcohol intoxication ( 31 ); one included a case of POD ( 32 ); one reported no recall of dream mentation ( 33 ); one was a study of NREM dream mentation but not in the context of NREM parasomnias ( 34 ); and the remaining did not describe clear dream mentation ( 35 - 37 ).…”
Section: Resultsmentioning
confidence: 99%
“…In the literature, we have found only one case presenting with pain in association with a NREM parasomnia. 3 In the previous case report, no associated psychological, physical, or sexual trauma was disclosed. The patient recalled an accompanying sense of "fi ghting to stay alive" associated with intense panic and fast, regular palpitations.…”
Section: Discussionmentioning
confidence: 99%
“…3 We report a case of severe NREM parasomnia manifested by the previously unreported feature of lancinating throat pain.…”
Section: A S E R E P O R T Smentioning
confidence: 99%
See 1 more Smart Citation